Some Lessons from Using Static Analysis and Software Model Checking for Bug Finding - Musuvathi, Madan; Engler, Dawson R. (Electronic Notes in Theoretical Computer Science, 2003)
This paper grew out of our experiences with software model checking after several years of using static analysis to find errors.